Verification of the effects of Lignohumat B and Synergin® in organic strawberry production - Šárka Kremláčková; Petr Salaš; Stanislav Boček (Acta Universitatis Agriculturae et Silviculturae Mendelianae Brunensis, 2011)
The objective of this work is to determine the effect of auxiliary plant preparations such as Lignohumat B and biostimulant Synergin® on yield and quality of strawberry production. The two year trial was carried out on two plots of the Horticultural Faculty in Lednice Mendeleu. Among different cultivars the ‘Honeoye’ and ‘Symphony’ have been selected, they are recommended for organic production. Lignohumat B was applied to strawberries according to the manufacturer instructions: soaking the root system, watering after planting, spraying on the leaves two weeks before flowering and after flowering in 1% concentration. Synergin® was applied before flowering by means of foliar sprayer and two weeks after flowering in the recommended dose of 3 l.ha−1.In trial No. 1, the average yield for the two years 2007 and 2008 was 24.69 t.ha−1 for the ‘Honeoye’ cultivar and 35.48 t.ha−1 for ‘Symphony’. The average yield per plant for ‘Honeoye’ cultivar was 296.16 g and for ‘Symphony’ it was 426.36 g. Trial No. 2 was carried out in 2008−2009, the yield for ‘Honeoye’ cultivar was 35.91 t.ha−1 and for ‘Symphony’ variety 36.5 t.ha−1. On average for two years trials, the yield of one plant for ‘Honeoye’ cultivar was 429.27 g and for ‘Symphony’ cultivar 439.02 g. The result is that the auxiliary plant preparations (Lignohumat B and Synergin®) had a limited effect on strawberry plants and the results were not statistically significant. Experiments demonstrate that the two selected cultivars can be recommended to the organic production.